Acoustic cavities in 2D heterostructures - Maxim K. Zalalutdinov; Jeremy T. Robinson; Jose J. Fonseca; Samuel W. LaGasse; Tribhuwan Pandey; Lucas R. Lindsay; Thomas L. Reinecke; Douglas M. Photiadis; James C. Culbertson; Cory D. Cress; Brian H. Houston (Nature Communications, 2021)
Here, authors report on acoustic cavities in 2D materials operating in the 50–600 GHz range and show that quality factors approach the limit set by lattice anharmonicity. Functionality expanded by heterogeneities (steps and interfaces) is demonstrated through coupled cavities and frequency comb generation.